HepG2 spheroids cultured in alginate microcapsules as a model for exploring mitochondrial and glycolytic metabolism using the Seahorse XFe24 Analyzer - Miranda, Raul Ghiraldelli; Machado, Ivo F.; Rolo, Anabela Pinto; Dorta, Daniel Junqueira; Palmeira, Carlos Manuel Marques (Taylor & Francis, 2025)
Mitochondria are affected by chemical substances and play a critical role in drug-induced liver injury (DILI). Chemical substances can have a significant impact on various cellular processes, such as the disruption of oxidative phosphorylation, oxidative stress, and alteration of glucose metabolism. Given the consequences of these effects, it is crucial to understand the molecular pathways of chemical substances in the context of hepatotoxicity to prevent and treat DILI. In this regard, the Seahorse XFe24 Analyzer is a valuable tool for assessing mitochondrial bioenergetics and glucose metabolism. The Mito Stress Test and Glycolytic Rate Assay allow real-time assessment of the metabolic state after chemical exposure. Additionally, HepG2 spheroids have emerged as an important alternative tool for assessing hepatotoxicity, as they provide results that are more comparable to those found in humans than monolayer cultures or animal tests (such as rodent tests). By integrating these two powerful tools, it is possible to bridge the gap between animal and human tests, resulting in more reliable results in the assessment of human hepatotoxicity and DILI. However, because of the high variability in characteristics between 3D cultures (such as spheroids and organoids), XF analyzer assays are not well optimized for use with HepG2 spheroids. Here, we describe a streamlined and optimized protocol for performing the Mito Stress Test and Glycolytic Rate Assay using HepG2 spheroids cultured in alginate microcapsules in the Seahorse XFe24 Analyzer.